2013
DOI: 10.1182/blood-2013-02-484444
|View full text |Cite
|
Sign up to set email alerts
|

Clonal genetic and hematopoietic heterogeneity among human-induced pluripotent stem cell lines

Abstract: Key Points Normal induced pluripotent stem cells exhibit donor-specific gene expression signatures and the capacity for hematopoietic development. CNVs acquired during reprogramming or selection of rare CNVs present in the starting cell population may alter iPSC developmental potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 18 publications
2
63
0
Order By: Relevance
“…During the course of this study, serial Western blotting for GATA1 showed that female GATA1s iPSC lines did not undergo reactivation of the lyonized X chromosome, which can occur during iPSC passage (19,22). Genetic and epigenetic variation between different iPSC lines may alter their developmental potential, including hematopoietic (23,24). We controlled for this by systematically analyzing multiple iPSC clones from different individuals of the same relevant genotype ( Figure 1, C and D, n = 6 GATA1s and 12 WT GATA1) and isogenic lines from TMD blasts (T21/GATA1s) and normal blood cells (T21/WT GATA1) of the same DS patients (n = 2 different subjects, Supplemental Table 1 and Figure 1, G and H).…”
Section: Generation Of Ipscsmentioning
confidence: 81%
“…During the course of this study, serial Western blotting for GATA1 showed that female GATA1s iPSC lines did not undergo reactivation of the lyonized X chromosome, which can occur during iPSC passage (19,22). Genetic and epigenetic variation between different iPSC lines may alter their developmental potential, including hematopoietic (23,24). We controlled for this by systematically analyzing multiple iPSC clones from different individuals of the same relevant genotype ( Figure 1, C and D, n = 6 GATA1s and 12 WT GATA1) and isogenic lines from TMD blasts (T21/GATA1s) and normal blood cells (T21/WT GATA1) of the same DS patients (n = 2 different subjects, Supplemental Table 1 and Figure 1, G and H).…”
Section: Generation Of Ipscsmentioning
confidence: 81%
“…23 iPSCs were differentiated into megakaryocytes as previously described. 24 For all, large megakaryocytes were isolated using a 2-step bovine serum albumin density gradient described for murine megakaryocytes 19 and counted by hematocytometer before retro-orbital infusion in 200 mL phosphate-buffered saline (PBS; Invitrogen). Similar AMC growth conditions were used to isolate EV-PLPs.…”
Section: Methodsmentioning
confidence: 99%
“…12 Hemizygous insertions were confirmed by using Southern blot analysis 12,13 (supplemental Figure 2B-C). iPSCs were differentiated into hematopoietic progenitor cells (HPCs) and megakaryocytes by using a previously described protocol 14 and were analyzed for both quantitative gene expression and surface marker expression. The functionality of agonist-stimulated megakaryocytes was evaluated by flow cytometry using PAC-1 antibody, 15 which binds specifically to the active conformation of integrin aIIbb3 and The publication costs of this article were defrayed in part by page charge payment.…”
Section: Methodsmentioning
confidence: 99%